Antioxidant activity of oily extract obtained from Lippia origanoides improves the quality of bovine embryos produced in vitro - N.V. Sollecito; E.C.M. Pereira; J.G.V. Grázia; B.P. Neves; B.V.R. Couto; V.B. Andrade; M.S. Miranda; J.K.R. Silva; A.M. Borges (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim of this study was to evaluate the supplementation of embryo culture medium with antioxidant obtained from oily extract of Lippia origanoides on in vitro blastocyst development and quality. Oocytes collected from slaughterhouse ovaries were matured and fertilized in vitro following standard laboratory procedures. Zygotes were cultured in SOF medium supplemented according to the following treatments: T1 embryo culture medium without antioxidant supplementation; T2)50μM/mL Cysteamine; T3)2.5μg/mL; T4)5.0μg/mL and T5)10.0μg/mL of antioxidant obtained from oily extract of Lippia origanoides. On the seventh day of culture, the blastocysts were fixed and evaluated for apoptosis rates, number of total cell and inner cell mass cells by means of the TUNEL Test. The use of antioxidants during cultivation did not increase (P> 0.05) the final blastocyst production rate. The treatments T2, T3, T4 and T5 had the lowest (P< 0.05) apoptotic indexes (4.5±1.1%, 8.4±2.5%, 3.4±1.1% and 5.5±0.9%, respectively) when compared to T1 treatment (10.0±1.4%). The number of inner cell mass did not differ (P> 0.05) among embryos from different treatments. The addition of antioxidant obtained from oily extract of Lippia origanoides reduces the apoptosis rate and improves the quality without increasing the total in vitro production of bovine embryos.